Pelatihan dan Bimbingan Pengelolaan Keuangan dan Pajak pada Sekayuh Indonesia - Lina Said; Yane Devi Anna (Jurnal Dharma Bhakti Ekuitas, 2025)
Small and medium-sized enterprises (SMEs) occupy a significant position within the Indonesian economy. The Sekayuh Indonesia MSMEs are engaged in the production and sale of fashion products and bags. The recognition and utilization of these products by individuals, companies, government agencies, and state-owned enterprises is evidenced by the increasing demand and sales of their products.  In conjunction with the annual growth in turnover, it is imperative to establish and maintain transparent and accurate financial records. As a partner, Sekayuh Indonesia encounters challenges in its financial management due to the lack of adherence to standards for bookkeeping and financial reporting, particularly with regard to the calculation and reporting of MSME personal taxes. The community service team offers partners assistance in the form of training and guidance on the preparation of financial and tax reports. This is done with the objective of ensuring the future management of the business is conducted in a manner that is both transparent and accountable.  As a result, the partner has been able to enhance its financial recordkeeping by implementing a system for tracking monthly income and expenses, thereby facilitating the calculation of profit or loss on a monthly basis. Moreover, it is anticipated that partner will fulfill its tax obligations in accordance with the relevant regulations.  The Partner has the potential to expand its business operations, creating employment opportunities and investing in equipment for production. With a focus on product quality and unique advantages, the company has the capacity to achieve further growth and success. Keywords: SMEs, bookkeeing, financial statement, tax.   Abstrak UMKM menempati posisi penting dalam perekonomian Indonesia. UMKM Sekayuh Indonesia (disingkat “SKYH”) bergerak di bidang produksi dan penjualan fashion dan tas, seperti pakaian olahraga, tas ransel, tas pinggang, tas sepeda, tas travel, tas laptop, pouch, dompet, dan souvenir berbentuk tas atau dompet lainnya, kaos, jaket, dll.  Pengakuan dan pemanfaat produk-produk ini oleh perorangan, perusahaan, instansi/lembaga pemerintah, maupun BUMN, dibuktikan dengan meningkatnya permintaan dan penjualan produk mereka.  Sehubungan dengan pertumbuhan omset tahunan, sangat penting untuk membuat dan memelihara catatan keuangan yang transparan dan akurat.   Mitra SKYH Indonesia menghadapi tantangan dalam pengeloaan keuangannya yang sesuai pedoman SAK EMKM/ETAP dan penghitungan serta pelaporan pajak orang pribadi UMKM.  Pengabdian kepada masyarakat memberikan bantuan kepada Mitra dalam bentuk pelatihan dan bimbingan penyusunan laporan keuangan dan pajak.  Hal ini dilakukan dengan tujuan untuk memastikan pengelolaan bisnis di masa depan dilakukan dengan cara yang transparan dan akuntabel. Sebagai hasil pengabdian masyarakat ini, mitra telah mampu meningkatkan pencatatan keuangannya dengan menerapkan pencatatan pemasukan dan pengeluaran bulanan, sehingga memudahkan penghitungan laba atau rugi setiap bulannya.  Selain itu, diharapkan pula mitra dapat memenuhi kewajiban perpajakannya sesuai dengan ketentuan yang berlaku.  Mitra memiliki potensi untuk memperluas operasi bisnisnya, menciptakan kesempatan kerja dan berinvestasi dalam peralatan untuk produksi. Dengan fokus pada kualitas produk dan keunggulan yang unik, perusahaan memiliki kapasitas untuk mencapai pertumbuhan dan kesuksesan lebih lanjut. Kata kunci: UMKM, pembukuan, laporan keuangan, pajak.